Skeletal Muscle Interleukin-6 Regulates Hepatic Cytochrome P450 Expression: Effects of 16-Week High-Fat Diet and Exercise. (20th November 2017) - Knudsen, Jakob G; Bertholdt, Lærke; Gudiksen, Anders; Gerbal-Chaloin, Sabine; Rasmussen, Martin Krøyer
Abstract: High-fat diet (HFD) induces several changes to the pathways regulating energy homeostasis and changes the expression of the hepatic cytochrome p450 (Cyp) enzyme-system. Despite these pervious findings, it is still unclear how the effects of HFD and especially HFD in combination with treadmill running affect hepatic Cyp expression. In this study, we investigated the mRNA and protein expression of selected Cyp's in mice subjected to 16 weeks of HFD and treadmill running. To understand the regulatory mechanisms behind the exercise-induced reversion of the HFD-induced changes in Cyp expression, we used a model in which the exercise-induced myokine and known regulator of hepatic Cyp's, interleukin-6 (IL-6), were knocked out specifically in skeletal muscle. We found that HFD increased the mRNA expression of Cyp1a1 and Cyp4a10, and decreased the expression of Cyp2a4, Cyp2b10, Cyp2e1, and Cyp3a11. HFD in combination with treadmill running reversed the HFD increase in Cyp4a10 mRNA expression. In addition, we observed increased Cyp1a and Cyp3a protein expression as an effect of exercise, whereas Cyp2b expression was lowered as an effect of HFD. IL-6 effected the response in Cyp3a11 and Cyp1a expression. We observed no changes in the content of the aryl hydrocarbon receptor, constitutive androstane receptor, pregnane X receptor, or peroxisome proliferation activator receptor alpha. In conclusion, we show that both HFD and exercise in HFD-fed animals can regulate hepatic Cyp expression and that changes in Cyp3a in response to HFD and exercise are dependent on skeletal muscular IL-6.